2022
DOI: 10.1101/2022.07.12.22277336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Variant Vaccine Boosters Trial: Preliminary Analyses

Abstract: Background: Protection from SARS-CoV-2 vaccines wanes over time and is compounded by emerging variants including Omicron subvariants. This study evaluated safety and immunogenicity of SARS-CoV-2 variant vaccines. Methods: This phase 2 open-label, randomized trial enrolled healthy adults previously vaccinated with a SARS-CoV-2 primary series and a single boost. Eligible participants were randomized to one of six Moderna COVID19 mRNA vaccine arms (50 mcg dose): Prototype (mRNA-1273), Omicron BA.1+Beta (1 or 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Secondly, if switching to a variantmodified vaccine, how important is it that the immunogen in the variant-modified vaccine is antigenically closely related to the spike protein of the circulating variant? We analysed the data from 8 reports that included a direct comparison of immunogenicity of an ancestralbased vaccine with a variant-modified vaccine [1][2][3][4][5][6][7][8] . They included data from the Sanofi-GlaxoSmithKline, Moderna, and Pfizer-BioNTech vaccine constructs incorporating the Beta, Delta, or Omicron BA.1 spike proteins (either alone or in combination with each other or the ancestral variant spike proteins).…”
Section: Main Textmentioning
confidence: 99%
“…Secondly, if switching to a variantmodified vaccine, how important is it that the immunogen in the variant-modified vaccine is antigenically closely related to the spike protein of the circulating variant? We analysed the data from 8 reports that included a direct comparison of immunogenicity of an ancestralbased vaccine with a variant-modified vaccine [1][2][3][4][5][6][7][8] . They included data from the Sanofi-GlaxoSmithKline, Moderna, and Pfizer-BioNTech vaccine constructs incorporating the Beta, Delta, or Omicron BA.1 spike proteins (either alone or in combination with each other or the ancestral variant spike proteins).…”
Section: Main Textmentioning
confidence: 99%
“…18 Even within the Omicron variant, BA.4/BA.5 sub-variants also largely evaded the neutralization induced by BA.1 infection or vaccination, with a 2.6-8.0-fold drop in the nAb titers. [19][20][21] Therefore, there is an urgent need to develop broad-spectrum vaccines to fight against immune-evasive variants.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the inactivated virus-based, mRNA-based, and recombinant protein-based platforms, multiple updated vaccines specific to Beta, Delta, Omicron BA.1 or Omicron BA.2 have been developed. 20,[22][23][24][25][26][27][28] Results of animal studies and clinical trials have shown that these variant-targeting vaccines could induce higher nAb responses than the ancestral vaccine against these specific variants. Furthermore, variant-specific vaccines along with prototype vaccines have been used in combination to achieve cross-neutralizing responses against divergent SARS-CoV-2 strains (ClinicalTrials.gov identifier: NCT05365724, NCT05381350, NCT05382871).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the recommendation by the FDA for including the Omicron variant in COVID-19 vaccines (4). However, issues have been raised about the value of adding Omicron to the vaccine based on data showing only modest differences between antibody responses after booster immunization with Omicron versus WA1 (5-7). Questions also remain about which Omicron variant(s) should be used and whether the WA1 strain should still be kept in the updated vaccine.…”
Section: Figurementioning
confidence: 99%